Stated and revealed investment decisions concerning retail structured products - Döbeli, Barbara; Vanini, Paolo (Journal of Banking & Finance, 2010)
We analyze the investment behavior of private clients with regard to retail structured products. To ascertain their stated and revealed preferences, we use a questionnaire and a field experiment. The real product issued in the field experiment is comparable to the hypothetical product in the questionnaire in terms of both payoff and communication. We find that a product described in simple words strongly motivates people to invest in structured products for the first time, and also eliminates gender differences. However, the real product attracts far fewer first-time buyers than we expected from the questionnaire results.